Symphysis Pubis Osteomyelitis with Bilateral Adductor Muscles Abscess - Saad M. Alqahtani; Fan Jiang; Bardia Barimani; Marie Gdalevitch (Case Reports in Orthopedics)
Osteomyelitis of the pubis symphysis is a rare condition. There have been various reports in the literature of inflammation and osteomyelitis as well as septic arthritis of pubic symphysis. However, due to the fact that these conditions are rare and that the usual presenting symptoms are very nonspecific, osteomyelitis of the pubic symphysis is often misdiagnosed, thus delaying definitive treatment. We present a case that to our knowledge is the first case in literature of osteomyelitis of the pubic symphysis in a 17-year-old boy with juvenile idiopathic arthritis (JIA), which was initially misdiagnosed and progressed to bilateral adductor abscesses. A high suspicion of such condition should be considered in a JIA patient who presents with symphysis or thigh pain.